Influencing Factors on Radiotherapy Outcome in Stage I-II Glottic Larynx Cancer—A Multicenter Study - Elicin, Olgun; Ermiş, Ekin; Oehler, Christoph; Aebersold, Daniel M.; Caparrotti, Francesca; Zimmermann, Frank; Studer, Gabriela; Henke, Guido; Adam, Lukas; Anschuetz, Lukas; Ozsahin, Mahmut; Guckenberger, Matthias; et al. (Frontiers in Oncology, 2019)
Background and Purpose: Larynx cancer represents one of the most frequently diagnosed head and neck malignancies, which is most often confined to the glottic area. The aim of this study was to report the oncological outcome and identify prognostic factors in early-stage glottic squamous cell carcinoma treated with radiotherapy. Material and Methods: Patients (n = 761) diagnosed and treated in 10 centers between 1990 and 2015 were retrospectively analyzed. Probabilities of loco-regional control (LRC) and overall survival (OS) were calculated and possible prognostic factors were analyzed using Cox proportional hazards models. Results: The median follow-up was 63 months (range: 2–243). Three hundred and sixty-four, 148 and 249 patients had cT1a, cT1b, and cT2 stage I-II disease, respectively. Five and 10-years LRC/OS rates in the whole cohort were 83/82% and 80/68%, respectively. Three patients developed distant recurrences. In univariate analysis, male sex (HR: 3.49; 95% CI: 1.47–11.37; p < 0.01), T2 vs. T1a (HR: 1.62; 95% CI: 1.08–2.43; p = 0.02) and anterior commissure involvement (ACI) (HR: 1.66; 95% CI: 1.38–2.45; p < 0.01) were associated with impaired LRC. In multivariate analysis, male sex (HR: 3.42; 95% CI: 1.44–11.17; p < 0.01) and ACI (HR: 1.51; 95% CI: 1.01–2.28; p = 0.047) remained poor prognostic factors. No relation of treatment technique and biologically equivalent dose (BED) to oncological outcome was identified except for higher BED10(L = 25; T = 1) yielding better LRC in T1a tumors (p = 0.04) in univariate analyses. Conclusion: Our results highlight the negative impact of ACI on tumor control. A less-expected finding was the impact of sex on tumor control. Further research is needed to validate its prognostic value and investigate any related biologic or behavioral factors, which may be modified to improve oncologic outcome.